ANALISIS FAKTOR YANG MEMPENGARUHI PEMBIAYAAN BAGI HASIL MUDHARABAH PADA BANK UMUM SYARIAH - Choirudin, Ahmad; Praptoyo, Sugeng (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research analyzes some factors which give influence to the mudharaba financing. This researchis aimed to tests the Deposits of Mudharabah (DM), Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Operating Expenses to Operating Income (BOPO) to the Mudharabah Financing (PM). The population in this researchhas been obtained by using purposive sampling method on Islamic commercial banks in Indonesia in 2012-2015 periods. Based on the predetermined criteria then 10 Islamic commercial banks have been selected as samples. The datahas been obtained from the quarterly reports of syariah banks. The observation objects are 160 data. The analysis method has been carried out by using multiple linear regression with SPSS software (Statistics Product and Service Solutions) 22.0 version. Based on the result of multiple linear regression analysis, the results of this research indicates that the deposits of mudharaba give positive influence to the mudharaba financing, capital adequacy ratio give positive influence to the mudharaba financing, financing to deposit ratio give positive influence to the mudharaba financing, non-performing financing give negative influence to the mudharaba financing, costs operating to operating income (BOPO) does not giveany influenceto the mudharaba financing.Keywords: DM, CAR, NPF, FDR, PM.